2018
DOI: 10.1242/dmm.034850
|View full text |Cite
|
Sign up to set email alerts
|

Identification of brain metastasis genes and therapeutic evaluation of histone deacetylase inhibitors in a clinically relevant model of breast cancer brain metastasis

Abstract: Breast cancer brain metastases remain largely incurable. Although several mouse models have been developed to investigate the genes and mechanisms regulating breast cancer brain metastasis, these models often lack clinical relevance since they require the use of immunocompromised mice and/or are poorly metastatic to brain from the mammary gland. We describe the development and characterisation of an aggressive brain metastatic variant of the 4T1 syngeneic model (4T1Br4) that spontaneously metastasises to multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…In this study, we reported an orthotopic model of spontaneous ERBB2 + BC BrM that can be used to evaluate therapeutic approaches targeting both the primary tumor and distant metastases together, suggesting its high clinical relevance. Previously, an orthotopic mouse model of BrM using triple-negative cell lines MDA-MB-231 and 4T1 have been reported in NSG and BALB/c mice, respectively, which are suitable for therapeutic modalities against TNBC [49][50][51][52]. In the ERBB2 + BC subtype, both intracardiac and intracarotid models have been used for the evaluation of therapeutic modalities against BC BrM [24,25,53].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we reported an orthotopic model of spontaneous ERBB2 + BC BrM that can be used to evaluate therapeutic approaches targeting both the primary tumor and distant metastases together, suggesting its high clinical relevance. Previously, an orthotopic mouse model of BrM using triple-negative cell lines MDA-MB-231 and 4T1 have been reported in NSG and BALB/c mice, respectively, which are suitable for therapeutic modalities against TNBC [49][50][51][52]. In the ERBB2 + BC subtype, both intracardiac and intracarotid models have been used for the evaluation of therapeutic modalities against BC BrM [24,25,53].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous (IV) inoculation (tail vein injection) is uncommon due to the low incidence of BM formation and inevitable lung metastases. Spontaneous models frequently form a single lesion in the BM 58 , reflecting the actual process from tumor occurrence to metastasis. However, extensive use is hindered by the prolonged experimental period and metastases throughout the body 68 .…”
Section: Establishment Of Am-bm and The Intervention Time Of Rtmentioning
confidence: 99%
“…Numerous cell-surface molecules located on the tumor cell or endothelial surface are implicated in the formation and outgrowth of brain metastases (Table 4 ). These include ALCAM [ 175 177 ], PECAM1 [ 178 ], L1CAM [ 179 , 180 ], melanotransferrin [ 181 ], E-Selectin [ 155 , 156 , 182 186 ], and E-cadherin/ N-cadherin [ 187 190 ].…”
Section: Breaking and Altering: Mechanisms Facilitating Tumor Cell Ex...mentioning
confidence: 99%